The Effect of Postoperative Tranexamic Acid and Dexamethasone on Quality of Recovery After Arthroscopic Rotator Cuff Repair: a Double-Blinded, Randomized Controlled Trial - Jiang X; Xu C; Yuan C; Gao W; Liu W; Wang Y; Wang H; Yu W; He Y (Journal of Pain Research)
Xiping Jiang,1,* Cheng Xu,2,* Chenrui Yuan,1,* Wenliang Gao,3 Wencai Liu,1 Yifei Wang,1 Haiming Wang,1 Weilin Yu,1 Yaohua He1,4 1Department of Orthopedic Surgery, Shanghai Sixth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200233, People’s Republic of China; 2Department of Anesthesiology, Shanghai Sixth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200233, People’s Republic of China; 3Department of Orthopedics, Longyan First Affiliated Hospital of Fujian Medical University, Longyan, Fujian, 364000, People’s Republic of China; 4Department of Orthopedic Surgery, Jinshan District Central Hospital Affiliated to Shanghai University of Medicine & Health Sciences, Jinshan Branch of Shanghai Sixth People’s Hospital, Shanghai, 201500, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weilin Yu; Yaohua He, Department of Orthopedic Surgery, Shanghai Sixth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200233, People’s Republic of China, Tel +86 021 64369181, Email yuweilin2008@163.com; heyaohua@sjtu.edu.cnPurpose: Arthroscopic rotator cuff repair (ARCR) commonly results in significant postoperative pain. Adjuncts like dexamethasone (DEX) and tranexamic acid (TXA) are used to enhance postoperative recovery. This study aimed to determine whether the combined application of TXA and DEX could improve postoperative recovery during the first 24 hours in ARCR patients. Our goal is to relieve the acute postoperative pain and promote fast recovery and rapid discharge for ARCR patients.Patients and Methods: Ninety-six patients who underwent ARCR from December 2023 to March 2024 were enrolled in this double-blinded, randomized control trial (Registration number, ChiCTR2300078507). Patients were randomized to intravenously receive 200mL of normal saline (control group), 200mL of 1g TXA in saline (TXA group), or 200 mL of 1g TXA and 5mg DEX in saline (TXA+DEX group) within 2 hours postoperatively. The primary outcome was the Quality of Recovery-15 (QoR-15) score at 24 hours post-surgery. Secondary outcomes included mean visual analog scale (VAS) scores every four hours within 24 hours, postoperative blood test results the day after surgery, and American Shoulder and Elbow Surgeons (ASES) score at 3 months postoperatively.Results: No significant differences in QoR-15 scores at 24 hours were observed among the groups [control, 127.0 (112.8, 138.0); TXA, 125.0 (116.5, 136.8); TXA+DEX, 132.0 (120.3, 140.8), p = 0.176]. VAS scores at 5– 8 (placebo vs TXA+DEX, p = 0.014; TXA vs TXA+DEX, p = 0.002), 9– 12 (placebo vs TXA+DEX, p = 0.008; TXA vs TXA+DEX, p < 0.001), and 13– 16 (placebo vs TXA+DEX, p = 0.035; TXA vs TXA+DEX, p = 0.013) hours postoperatively showed a significant decrease for the TXA+DEX group compared with the control or TXA group. There were no significant differences in postoperative blood test results and ASES score at 3 months postoperatively.Conclusion: Postoperative application of TXA alone could not facilitate postoperative recovery during the first 24 hours in ARCR patients. Although the combination of TXA and DEX presented better levels of postoperative pain between 5 and 16 hours than the control and TXA alone, it did not significantly improve postoperative recovery quality. Further large-scale and multi-center investigation is required to determine if the combined application of TXA and DEX or TXA alone is beneficial for postoperative recovery in ARCR patients.Keywords: postoperative pain, arthroscopy, rotator cuff tear, QoR-15, TXA, DEX